PENGARUH KOMUNIKASI DAN KEPRIBADIAN TERHADAP KEPUASAN MASYARAKAT MELALUI KUALITAS PELAYANAN PEGAWAI KANTOR DESA DRIYOREJO - Erlinda Sumitasari Yolanda; Brillian Rosy (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to determine the effect of communication variables and personality variables on community satisfaction variables through service quality variables. The type of research used is descriptive research through a quantitative approach with data collection techniques through questionnaires and the data analysis technique used is path analysis with the help of the SPSS version 26 application. X1) and Personality (X2) have a direct effect on the Service Quality variable (Y), there is only a direct influence on the Communication variable (X1) and the Service Quality variable (Y) on the Community Satisfaction variable (Z), there is no indirect effect on the variable Communication (X1) on the Community Satisfaction variable (Z) through the Service Quality variable (Y), and there is an indirect influence on the Personality variable (X2) on the Community Satisfaction variable (Z) through the Service Quality variable (Y). Based on the results of the study, it is hoped that the Driyorejo Village office employees can improve service quality, improve communication and personality in order to create better Driyorejo Village community satisfaction and researchers hope that further research can add other variables to make research more accurate.